(3EjVGM SbW GdRfO hVhFgs - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3CHh GdYdGA GdeYQj , CHh GdYdGA CMeO Hf YHO Gddg Hf SdjeGf GdJfhMj GdeYQj,J (B449 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf aCffi deG MVQJ GHG GdYdGA GdJfhNi bQCJ Ydjg cJGHkG ef cJH GddZI hTjFkG ef JUGfjag s
(3BNQgG (B:s
(3cCfc GdHOQ hGdOfjG efGRdg aeG Jdbjc EdG djdI OGQ s
(3YdjgG eYGQVI SfI (B474s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B290s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs